1993
DOI: 10.1007/bf01969269
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the cortical epithelium of the rat thymus after in vivo exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is known for inducing cortical atrophy in the rat thymus. The present study was conducted to provide ultrastructural evidence for the cortical epithelium to be a target for TCDD in vivo. Juvenile male Wistar rats were orally intubated once with either 50 or 150 micrograms/kg TCDD and killed 4 or 10 days thereafter. Major changes were found in the cortical thymic epithelium. First, a relative shift occurred from "pale" to darker cortical epithelial cell types, as judge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Histopathologic effects of PCN 66 and 67 in the present study were observed in the liver (hepatocellular hypertrophy, fatty change, necrosis, and inflammation) and thymus (atrophy) and were consistent with effects observed for TCDD (hepatocellular hypertrophy and thymic atrophy) and previous studies of TCDD (De Waal et al 1993). Effects of PCNs on hepatic fatty change, necrosis, and inflammation were not seen with TCDD in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Histopathologic effects of PCN 66 and 67 in the present study were observed in the liver (hepatocellular hypertrophy, fatty change, necrosis, and inflammation) and thymus (atrophy) and were consistent with effects observed for TCDD (hepatocellular hypertrophy and thymic atrophy) and previous studies of TCDD (De Waal et al 1993). Effects of PCNs on hepatic fatty change, necrosis, and inflammation were not seen with TCDD in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the ultrastructure of the human thymic epithelium, Van De Wijngaert and coworkers (1984) likewise have postulated that morphologically distinct EC subtypes represent sequential stages in a differentiation process. Our recent ultrastructural studies on alterations of the rat thymic epithelium after chemical exposure suggest a similar phenomenon (De Waal et al, 1993b).…”
Section: Discussionmentioning
confidence: 67%
“…The cellular component of the cTEC meshwork, also known as "cytoreticulum", is identified in both OTO-SEM and TEM by the characteristic presence of cytoplasmic tonofilaments, vacuoles, and the occasional presence of desmosomes between interconnecting cTEC projections (Fig. S4), as reported [68][69][70][71][72] . These distinguishing epithelial features provide validation of cTEC identity, especially when they are projected in proximity to cTEC nuclei, or when the cytoplasmic projection is shown to bud off the cTEC on the same z-plane (Fig.…”
Section: Ultrastructural Topography Of the Ctec Networkmentioning
confidence: 70%